Agronomic assay of tomato (Lycopersicon esculentum M.) in greenhouse. - Borrego, Fernando (2006)
The main objective of this work was to determine the adaptation potential of tomato genotypes for greenhouse. Genotypes evaluated were: hybrids: Contessa, Summer Flavor 5000, Summer Flavor 6000, Celebrity, Bonita, Shady Lady, Sunbolt, Sunny, Heat Wave and Olympic; and the variety Flora Dade, as a check. The variables evaluated were: yield, agroclimatic and physiological. agroclimatic and physiological variables were determine in three evaluations in the crop cycle, at three times/day and two leaf positions, in each evaluation. Significant correlations were found (p≤0.05) between yield in t/ha and mean yield by plant, fruits by plant at harvest, and yield by plant, and between photosynthesis and water use efficiency. Principal component analysis showed first five components have an Eigenvalue greater than one, explaining the first three with a 72% of total variance. The first component, with a 36% of total variance is due to “The yield characteristics” component two, with a 23% of total variance, is due to “internal temperature regulation characteristics” and component five, with a 7.4% of variation, to “photosyntates efficient production”. Multiple linear regression analysis difference was significant (p<0.01). Yield in t/ha was explained by the multiple linear equation (r2 =0.98) of four variables.